Successful systemic high‐dose ribavirin treatment of respiratory syncytial virus‐induced infections occurring pre‐engraftment in allogeneic hematopoietic stem cell transplant recipients. Issue 4 (20th May 2013) - Gueller, S.; Duenzinger, U.; Wolf, T.; Ajib, S.; Mousset, S.; Berger, A.; Martin, H.; Serve, H.; Bug, G.
Abstract Introduction Respiratory syncytial virus (RSV) is a frequent cause of respiratory tract infectious disease (RTID) in allogeneic hematopoietic stem cell transplant (HSCT) recipients associated with a high mortality once infection has progressed from upper RTID (URTID) to lower RTID (URTID). Aerosolized ribavirin (RBV) is considered a cornerstone of treatment, but is expensive and has toxic side effects on patients and staff. In this study, RSV infection was detected by polymerase chain reaction (PCR) from routinely collected throat swabs in HSCT patients. Infected individuals were treated according to an institutional protocol using intravenous (IV) RBV for patients with LRTID and oral ribavirin for URTID. Results RSV infection was diagnosed in 10 patients (median age 60 years) a median of 15 days after allogeneic HSCT for high‐risk acute myeloid leukemia. Five patients with LRTID received IV RBV within 7 days after HSCT, and 5 with URTID were treated with oral RBV 12–40 days after HSCT. One patient died of septic shock associated with Pseudomonas aeruginosa‐induced pneumonia 28 days after HSCT in prolonged neutropenia. All patients became RSV PCR negative on throat swabs within a median of 22 days from start of RBV. Despite severe lymphopenia, no patient treated for URTID progressed to LRTID. Neutrophil recovery was delayed in 3 patients. Conclusions We show that IV and oral RBV were efficacious in preventing progression and reducing mortality of RSV infection in this small series of allogeneic HSCT recipients. Randomized studies are not to be expected for this condition and therefore reporting case series could help in determining optimal RSV treatment.